Scholarly Viewpoints, featuring - T. King, Victor (Penerbit Universiti Sains Malaysia (USM Press), 2013)
What intrigues me about the ways in which the questions are posed is that they assume that we all work in disciplines. Since I have been given the welcome opportunity to present a "scholarly viewpoint" on Asia Pacific I would like to take a rather different tack. I want to make reference to certain recent developments in and contributions to what has come to be referred to as the multidisciplinary field of "area studies," which was promoted vigorously in the United States during the Cold War period and became increasingly important in institutional academic development in Western Europe, Australia, Japan and in Southeast Asia from the 1950s and 1960s. Since the 1970s, however, the popularity of this field of studies has tended to wane in the West, following the American departure from Indochina and then the end of the Cold War, and the questioning of the value and validity of teaching and research in regional studies by representatives of Western governments and the sponsors of scholarly activity. With the apparent undermining of the rationale for area studies, doubts were expressed about its theoretical and methodological rigour and whether or not area studies practitioners possessed the willingness and the academic capacity and expertise to respond to the major challenges posed by a fast-moving and globalising world. In short, opinions in the West began to turn against regional studies and it came to be seen as old-fashioned, conservative, parochial and poorly equipped to address and understand the social, cultural, economic and political issues and problems of a post-modern world. Paranoia, anxiety and a feeling of crisis set in among the area studies community, which resulted in an outpouring of publications in the 1970s and 1980s defending regions and those who studied them.